Diferencias generacionales en la construcción de la masculinidad, en hombres de la ciudad de Cali (2019)
In the present research work, called, "Generational differences in the construction of masculinity, in men of the city of Cali", it was intended to identify the way in which masculinity is constructed and signified, based on some milestones chronological in the life of the men proposed by Mara Viveros Vigoya. To explore these milestones, two age groups of men from the city of Cali were built, the first consisting of young men between 18 and 24 years of age, and the second, by adult men between 41 and 50 years of age, who they allowed the collection of information regarding the life experiences of each one and the gender roles that they have learned and appropriate, which made it possible to compare the similarities and differences between these generational groups with reference to the discourses and meanings corresponding to masculinity. In adults, on the one hand, there is a perception of the ideals of domination and power on the part of men, despite their attempts to make women part of responsibilities and decisions, on the other hand, young people see a greater acceptance regarding other forms of masculinity and gender. However, there are similarities between these two groups of men regarding the conceptions of the decrease in machismo and the equality between both genders, showing a generational change between them, which shows a progressive rupture of the hegemonic patterns of masculinity.